2017
DOI: 10.1038/s41598-017-01352-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated free triiodothyronine may lead to female sexual dysfunction in Chinese urban women: A hospital-based survey

Abstract: Research on female sexual dysfunction (FSD) is limited, especially in China, due to conservative culture and beliefs. There has been a dearth of FSD screening research in China since the optimal cutoff value of the Chinese version of the Female Sexual Function Index (CVFSFI) was determined in 2014. At the same time, the relationship between thyroid hormones and FSD has seldom been explored in Chinese women. Therefore, hospital-based research was conducted to elucidate FSD frequency and risk factors. Women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The health promotion center provided routine check-ups for each member. As described in previous study [ 18 ], all of approached women who meet criteria was included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The health promotion center provided routine check-ups for each member. As described in previous study [ 18 ], all of approached women who meet criteria was included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Included subjects were divided into two groups--ScHT and control group, according to thyroid hormone tests. The reference of thyroid hormone and antibody was the same in previous study [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a survey showed that 37.9 percent of the young and middle-aged women in Hong Kong had sexual dysfunction 41 . Similarly, Luo et al suggested that the incidence of sexual dysfunction in Chinese women was 26.5 percent, less than onethird 42 . Factors contributing to the diverse rates include various sociocultural backgrounds, sample selection, assessment methods, assessment procedures and different cutoff values.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the higher prevalence of hypothyroidism in women, there are more studies on sexual dysfunction in men than in women [ 5 ]. Although, in last years, some research has been conducted with larger samples of women with subclinical hypothyroidism [ 13 , 14 ], little attention has been paid to sexuality in women with primary hypothyroidism treated with levothyroxine [ 4 , 5 ]. Furthermore, the studies use small samples and the patients are not always euthyroid women [ 5 , 8 , 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%